Photoemission Studies of Si Quantum Dots with Ge Core: Dots formation, Intermixing at Si-clad/Ge-core interface and Quantum Confinement Effect - Yudi Darma (Institute for Research and Community Services (LPPM) ITB, 2008)
Spherical Si nanocrystallites with Ge core ( 20nm in average dot diameter) have been prepared by controlling selective growth conditions of low-pressure chemical vapor deposition (LPCVD) on ultrathin SiO2 using alternately pure SiH4 and 5% GeH4 diluted with He. XPS results confirm the highly selective growth of Ge on the pregrown Si dots and subsequently complete coverage by Si selective growth on Ge/Si dots. Compositional mixing and the crystallinity of Si dots with Ge core as a function of annealing temperature in the range of 550-800oC has been evaluated by XPS analysis and confirms the diffusion of Ge atoms from Ge core towards the Si clad accompanied by formation of GeOx at the Si clad surface. The first subband energy at the valence band of Si dot with Ge core has been measured as an energy shift at the top of the valence band density of state using XPS. The systematic shift of the valence band maximum towards higher binding energy with progressive deposition in the dot formation indicate the charging effect of dots and SiO2 layer by photoemission during measurements.